Flores, M. (2020). Estrella de dos puntas. Octavio Paz y Carlos Fuentes: crónica de una amistad. Ariel. - Alina Țiței-Avădanei (América sin Nombre)
Reseña de Alina Țiței-Avădanei: FLORES, M. (2020). Estrella de dos puntas. Octavio Paz y Carlos Fuentes: crónica de una amistad. Ciudad de México: Ariel, 654p, ISBN: 978-607-569-012-4.